The Economic Recovery Tax Act of 1981 : A Comparative Analysis of Its Impact on Inequality, Poverty, and Real Wages in the United States - Čurilla, Boris; Jordán, Lukáš; Tříska, Dušan, 1946-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines how the Economic Recovery Tax Act of 1981 (ERTA) affects income distribution, relative poverty, and real median wages in the United States, using Canada as a comparison country over 1975-1988. It deals with the question of whether a major supply-side tax cut brings broad gains in living standards or mainly benefits higher income groups. The analysis uses annual macroeconomic data and a two-country Difference-in Differences model with country and year fixed effects, Driscoll-Kraay standard errors, and controls for GDP per capita, inflation, unemployment, and social spending. The indicators include pre-tax and after-tax Gini coefficients, income shares of the top 1 %, top 10 % and bottom 50 %, a 60% median relative poverty rate, and the real median wage. The results show that ERTA is associated with higher pre-tax inequality and a falling income share of the bottom half of the distribution in the United States relative to Canada. Changes in after-tax inequality, relative poverty, and real median wages remain small and statistically insignificant. The thesis, therefore, nuances the common view of Reaganomics by documenting limited gains for middle and low-income households.
Vedoucí práce: Lukáš Jordán
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses